Making Unusual suspects - girls in gangs: a critical reflections on the ethics of cross-cultural filmmaking - Lamotte, Sophie (Centre for Film and Media Studies, 2024)
This research explores questions of ethics in cross-cultural documentary filmmaking in relation to making of the film “Unusual suspects: girls in gangs”. The film depicts the livedexperiences of three women who are or were involved in gangs and follows a police unit commander in her duties in fighting gang-related crime. The making of the film was characterised by cultural differences because I, the film maker, am a foreigner entering an arguably less privileged field with participants who could be considered vulnerable - both in terms of their socio-economic status and their safety. The mode of the documentary is observational, with elements of the participatory, based on encounters with the ‘Other' androoted in a desire to shine a light on a largely hidden issue that affects a lot of women in South Africa, and the Cape Flats specifically. The film's production prompted continual engagement with ethical questions. In this explication, which accompanies the film, I analyse my own practises and offer a set of suggestions based on my experience for making a documentary film with the intent of acknowledging one's positionality and overtly addressing issues of power differentials between the filmmaker and the people she represents.